Size distribution, characterization and risk assessment of particle-bound polycyclic aromatic hydrocarbons during haze periods in Phayao Province, northern Thailand - Pooltawee, Jaturaporn; Pimpunchat, Busayamas; Junyapoon, Suwannee (My University, 2017)
This study aims to investigate the concentrations and distributions of particulate matters and particle-bound polycyclic aromatic hydrocarbons (p-PAHs) in different inhalable fractions during haze periods in Phayao Province, northern Thailand and identify their possible emission sources through the characteristic ratios of selected PAHs, then determine an estimate of the potential lung cancer risk. The particulate samples were collected during haze periods between February 18 and April 8, 2014 and non-haze period from June 17 to 22, 2014 using an eight-stage cascade impactor. Each filter sample was weighed, ultrasonically extracted with acetonitrile, and then analyzed by SIM-GC-MS to identify 16 PAHs. The experimental results show that the concentrations of ultrafine (dae < 0.4 μm), fine (0.4 μm < dae < 2.1 μm), and coarse (dae > 2.1 μm) particles during haze periods were in the range of 14.98–26.52 μg m−3, 62.57–101.52 μg m−3, and 55.27–89.68 μg m−3, respectively; whereas, their concentrations of 16 PAHs were in the range of 7.82–36.06 ng m−3, 26.66–61.89 ng m−3, and 9.35–30.93 ng m−3, respectively. The p-PAH distribution profiles during the haze periods were bimodal in coarse and accumulation modes, which are closely related to their particle size distributions. The characteristic ratios of BaP/BgP and INP/(BgP+InP) adsorbed on ultrafine and fine particles were 0.81–0.88 and 0.38–0.86 and 0.54–0.57 and 0.44–0.52, respectively. The values of B[a]Peq observed during haze periods varied from 9.57 to 29.05 ng m−3. Estimated lifetime cancer risks during haze periods ranged from 8.324 to 25.27 additional cases per 10,000 people exposed, which is about 10 times higher than that during non-haze period.
Keywords: Carcinogenic; Haze periods; Inhalable particles; Lifetime cancer risk; PAHs; Size distribution